Factors Influencing the Extent and Quality of Corporate Social Responsibility Disclosure in Indonesian Shari’ah Compliant Companies - Fedi Ameraldo; Nazli Anum Mohd Ghazali (International Journal of Business and Society, 2021)
This study aims to assess the extent and quality of corporate social responsibility (CSR) disclosure practices of Shari’ah Compliant Companies (ShCCs) in Indonesia. Further, the study examines the factors influencing the extent and quality of CSR disclosure of ShCCs in Indonesia. A checklist comprising of 33 items was constructed to measure the extent and quality of disclosure. Using data from the year 2014 annual reports of 100 ShCCs in Indonesia, the results showed that the extent and quality of CSR disclosure among ShCCs in Indonesia were low with more than half of the sample companies scored less than 50% for extent of disclosure and all sample companies scored less than 50% for quality of disclosure. The multiple regression analysis revealed that award and leverage had an impact on the extent and quality of CSR disclosure. The findings indicate the need for improvement in the disclosure practice in annual reports of ShCCs. The relevant regulatory authority may issue guidelines and monitor companies’ compliance to the guidelines to assist companies in enhancing CSR disclosure. Continuous and concerted efforts by the regulatory authority and ShCCs are necessary to ensure achievement of social transparency and accountability. This in turn may propel the development of Islamic capital market to the next level.